Implementation of the Family Relationship Centres initiative : Attorney-General's Department [and] Department of Families, Housing, Community Services and Indigenous Affairs - Australian National Audit Office; Wilkinson, Alex.; Favre, Isabelle; Cummins, Kate.; Williamson, Nathan (Canberra, A.C.T. : Australian National Audit Office, 2010)
"The objective of the audit was to assess the effectiveness of the selection, implementation, operation and monitoring of FRCs by AGD and FaHCSIA. The three main criteria for this audit assessed whether AGD and FaHCSIA had effectively: planned and implemented the FRC initiative, including the FRC selection and funding processes; undertaken administration activities to guide the operation and progress of the FRC initiative towards meeting its objectives; and monitored, evaluated and reported on the performance of FRCs" -- ANAO web site.
"Audit team: Alex Wilkinson, Isabelle Favre, Kate Cummins, Nathan Williamson" -- P. 4.
Includes bibliographical references and index.
Also available in an electronic version via the Internet. Address as at 12/10/10: http://www.anao.gov.au/uploads/documents/2010-11%20Audit%20Report%20No%201.pdf
Also available online
Keywords: Family Relationship Centres (Program).; Australia. -- Attorney-General's Department -- Auditing; Australia. -- Department of Families, Housing, Community Services and Indigenous Affairs -- Auditing; Family mediation -- Australia; Family services -- Economic aspects -- Australia; Dispute resolution (Law) -- Australia; Law reform -- Australia; Family policy -- Australia